Expression of Small Integrin‐Binding LIgand N‐linked Glycoproteins (SIBLINGs) in the reparative dentin of rat molars. Issue 4 (6th February 2014) - Xie, Xiaohua; Ma, Su; Li, Changcheng; Liu, Peihong; Wang, Haixia; Chen, Li; Qin, Chunlin
Abstract Aim To analyze the expression and distribution of Small Integrin‐Binding LIgand N‐linked Glycoproteins (SIBLINGs) in reparative dentin (RepD). Methodology Cavities on the mesial surfaces of rat molars were prepared to expose the pulp, and a calcium hydroxide agent was applied to cap the exposed pulp. The molars with pulp capping were extracted at postoperative 1, 2, and 4 weeks. The immunolocalization of four SIBLINGs, dentin matrix protein 1 (DMP1), dentin sialoprotein (DSP), bone sialoprotein (BSP), and osteopontin (OPN) in RepD, was analyzed in comparison with reactionary dentin (ReaD) and primary dentin (PD). Results At two weeks after operation, the region of the exposed pulp formed a layer of reparative dentin bridge sealing the communication between the cavity and pulp chamber. Dentinal tubules in RepD were more irregular in shape and fewer in number than PD. At postoperative 2 and 4 weeks, RepD had lower levels of DMP1 and DSP than PD. BSP and OPN were present in RepD, but not in PD. RepD showed certain similarities to ReaD in the expression of SIBLINGs. Conclusions The reduced levels of DMP1 and DSP may be associated with the decreased number of dentinal tubules in RepD. The expression of BSP and OPN in RepD indicates that the odontoblast‐like cells were attempting to produce a hard tissue at a very rapid pace. These findings suggest that in response to the surgical injury, the newly differentiated odontoblast‐like cells altered their synthesis of the dentinogenesis‐related proteins and produced a hard tissue that is an intermediate between dentin and bone.